MODIFICATIONS OF CONSONANTS IN CONNECTED SPEECH ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the modifications of consonants in connected speech, highlighting key phonetic phenomena such as assimilation, elision, flapping, linking, and gemination. It elucidates how these processes enhance the fluency and naturalness of spoken language, contrasting them with isolated speech where words are pronounced distinctly. The implications of understanding these modifications are discussed in relation to language learning and teaching, emphasizing their importance for improving listening comprehension and pronunciation skills. Furthermore, the article addresses the relevance of these concepts in speech therapy and suggests avenues for future linguistic research. Ultimately, the article underscores the dynamic nature of speech and its significance in effective communication.